Severe Orbital Myiasis Caused by Chrysomya bezziana: A Case Report - Yu Siang Ng; Yuen Keat Gan; Leni Tupang (Türk Oftalmoloji Dergisi, 2021)

(untitled)
An 88-year-old woman was brought to the hospital immediately after her neighbours noticed that she was bleeding from her right eye. On examination, her right eye was phthisic with maggot infestation of her right orbit. Over a hundred live maggots were extracted using forceps. Computed tomography scan revealed the infestation was confined to the right orbit. The patient underwent exenteration of the right orbit under general anaesthesia. The species was identified by an entomologist as Chrysomya bezziana, which has aggressive larvae that eat living tissue. This case report demonstrates that orbital myiasis caused by C. bezziana poses a very real risk of intracranial invasion as they feed on living tissues. Adjacent tissue destruction can be very rapid and definitive treatment involves urgent removal of its larvae via surgical debridement. To our knowledge, we are reporting the first case of orbital myiasis from a patient in Malaysia. Therefore, our case report may be helpful in the management of similar case of orbital myiasis.